Executive Committee Minutes 2019-02-21 - Academic Senate:::::::::
Agenda – Approved. Minutes of 2/7/19 – Approved. Chair Report. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Associated Students Report. From EPC: New Concentration in Education Specialist Credential Early Childhood Studies – Approved for Senate consent calendar. From EPC: Policy on Off-Site Programs – Approved as a business item for the Senate. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Rep to SEC Report. Senate agenda approved.